Geospatial Technology Support in Small Academic Libraries: Time to Jump on Board. - Carrie M. Macfarlane; Christopher M. Rodgers (Issues in Science and Technology Librarianship, 2008)
Many librarians at small academic institutions have been wondering if they can, or even should, support the use of geospatial technology on their campuses. At the Middlebury College Libraries, we have developed a model of support for geospatial technology which we think might be versatile and transferable enough to try elsewhere. [ABSTRACT FROM AUTHOR]